Managing the learning environment - Morgan, Nancy Battista; Magna Systems, Inc. (Lake Zurich, Ill. : Magna Systems, 2006)
Focuses on how to develop a successful classroom. Discusses the important elements of instructional planning, how to establish classroom routines, arrange seating, maintain discipline, and deal with transitions
Title from title screen
Graphic design, Jenny Conway
Narrator: Ana Alvarez
Keywords: Lesson planning; Teacher effectiveness; Classroom management; Teacher-student relationships